TORAKOCHIRURGIAThe role of bilateral staged thoracotomy in pulmonary metastasectomy with the 1318 nm Nd:YAG laser - Gabryel, Piotr; Piwkowski, Cezary; Zieliński, Paweł; Kasprzyk, Mariusz; Roszak, Magdalena; Dyszkiewicz, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Background: Surgical treatment of lung metastases can be done with the use of classic or laser technique. Bilateral staged thoracotomy is one of the options of the operative approach to this treatment. Aim: The study was designed to assess the impact of bilateral, staged thoracotomy used for laser pulmonary metastasectomy on pulmonary function and postoperative complications. Material and methods: In this retrospective study we included 61 patients who underwent Nd:YAG laser bilateral metastasectomy by staged thoracotomy from year 2003 to 2010. We compared data from the first and second surgical procedures and analyzed spirometric values, number of metastases resected, intra-operative blood loss, day of chest tubes removal, length of hospital stay and perioperative morbidity. The time interval between procedures was 4 to 6 weeks. Results: There was no intra-operative or 30-day mortality. The number of lesions resected in consecutive procedures was similar (median 4, 1-25 lesions v. median 4, 1-30 lesions). The decline in spirometric values correlated with the number of lesions resected (p<0.05). There was no difference in post-operative complications between the first and the second procedure (17.4% v. 23.19%, p = 0.479), prolonged air leak (7.35% v. 13.24%, p = 0.221), reoperations due to complications (8.57% v. 1.43%, p = 0.073), blood loss (median 100 ml, 0-500 ml), chest tube duration (median 3, 2-25 days v. 4, 2-18 days) and hospital stay after surgery (median 7, 4-30 v. median 4, 4-35 days). Conclusions : The results indicate that bilateral staged thoracotomy and laser metastasectomy is a safe surgical procedure. Diminished FEV1 and FVC values after the first metastasectomy do not influence the number of complications after the second metastasectomy.